2016
DOI: 10.14405/kjvr.2016.56.4.215
|View full text |Cite
|
Sign up to set email alerts
|

Salt treatment for recovery of the mud loach, Misgurnus mizolepis from transport stress

Abstract: Due to the shortage of the fingerling/juvenile mud loach, Misgurnus mizolepis in Korea, these fish have been imported from China. However, the mortality rate during and after their transportation is very high. In this study, we examined various physiological and histological parameters to evaluate the effect of salt treatment on the survival and recovery of mud loaches in holding farms during the quarantine process. Glucose, osmolality, Na− , and histological changes were assessed for three different salinitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…In this study, virulence genes were identified in A. veronii strains obtained from rohu and catla fishes of Andhra Pradesh, India. Because of their rapid findings, PCR testing have been employed to determine the distribution of virulence genes (Yu et al, 2015). Because of the complexities of Aeromonas pathogenesis, no one suspected virulence associated factor can be identified as being responsible for specific symptom or disorder (Albert et al 2000).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, virulence genes were identified in A. veronii strains obtained from rohu and catla fishes of Andhra Pradesh, India. Because of their rapid findings, PCR testing have been employed to determine the distribution of virulence genes (Yu et al, 2015). Because of the complexities of Aeromonas pathogenesis, no one suspected virulence associated factor can be identified as being responsible for specific symptom or disorder (Albert et al 2000).…”
Section: Resultsmentioning
confidence: 99%